2018
DOI: 10.17586/2226-1494-2018-18-6-939-945
|View full text |Cite
|
Sign up to set email alerts
|

Study of acoustic signal during laser hydroacoustic processing of biological tissue by microsecond pulses of ytterbium-erbium glass laser radiation

Abstract: Предмет исследования. Представлены результаты исследования акустического сигнала, регистрируемого гидрофоном при воздействии на жидкость микросекундными импульсами лазерного излучения с длиной волны генерации 1,54 мкм и различной временной субструктурой. Обсуждается влияние энергии и временной субструктуры лазерного импульса на величину генерируемых перепадов давления в жидкости и эффективность удаления тканей катарактального хрусталика глаза. Метод. Микросекундные импульсы излучения лазера на иттербий-эрбиево… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…The pulses of Yb,Er:Glass laser radiation used for active delivery had a pronounced high-intensity "leading" spike ( Fig. 2(b)), which makes it possible to amplify the excitation hydroacoustic effects [20]. The energy of Yb,Er:Glass laser pulse varied in the range from 10 to 100 mJ, the pulse duration was 1.5 ± 0.5 µs (base).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pulses of Yb,Er:Glass laser radiation used for active delivery had a pronounced high-intensity "leading" spike ( Fig. 2(b)), which makes it possible to amplify the excitation hydroacoustic effects [20]. The energy of Yb,Er:Glass laser pulse varied in the range from 10 to 100 mJ, the pulse duration was 1.5 ± 0.5 µs (base).…”
Section: Methodsmentioning
confidence: 99%
“…The impact of pulsed radiation of near and middle IR lasers can initiate hydrodynamic effects in liquids. Experimental studies shown that irradiation of water with pulses of Er:YAG [15], Er:YSGG [17], Ho:YAG [17,18] and Yb,Er:Glass [19][20][21] lasers, whose wavelengths lie near its intense absorption bands, can stimulate the appearance of thermoelastic waves and cavitation processes in water, accompanied by the generation of pressure transients. In Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последнем случае обработка биоткани происходит в жидкой среде, а доставленные в переднюю камеру глаза через оптическое волокно лазерные импульсы стимулируют гидроакустические процессы, в том числе кавитацию, т. е. возникновение парогазовых полостей в жидкости. Эти процессы оказывают значительное влияние на эффективность разрушения катарактального хрусталика [2][3][4].…”
unclassified